Apelin-13 ameliorates chronic water-immersion restraint stress-induced memory performance deficit through upregulation of BDNF in rats. (23rd March 2019) - Shen, Pei; Yue, Qiang; Fu, Wan; Tian, Shao-Wen; You, Yong
Highlights: Apelin-13 ameliorates memory performance deficit in CWIRS rats. Apelin-13 did not affect locomotor activity and anxiety level in rat. Apelin-13 ameliorates hippocampal BDNF expression deficit in CWIRS rats. ANA-12 blocks the ameliorative effect of apelin-13 on memory performance deficit in CWIRS rats. Abstract: A large number of studies have demonstrated that the hippocampus has important influences on stress response and memory. The abundant expressions of apelin and its receptor APJ in the hippocampus may imply potential involvement of apelin/APJ signaling in modulating stress-related memory performance deficit. In our previous study, apelin-13 ameliorates memory performance deficit in acute stressed rats. Here, we further examined whether apelin-13 can ameliorate memory performance deficit in chronic stressed rats. Rats were exposed to chronic water-immersion restraint stress (CWIRS) for 4 weeks. After stress withdrawal, apelin-13 was intracerebroventricularly infused once a day for one week. The novel object recognition test (NORT) and Y-maze test (YMT), two hippocampus-dependent memory tasks, were performed to assess memory performance. We found that apelin-13 restored CWIRS-induced decline in the discrimination index and alternation ratio in NORT and YMT, respectively. Furthermore, apelin-13 ameliorated CWIRS-induced hippocampal BDNF expression deficit, and the TrkB receptor antagonist ANA-12 blocked the ameliorative effect of apelin-13 on memory performance deficit in CWIRS rats. The current observations indicate that apelin-13 ameliorates CWIRS-induced memory performance deficit through upregulation of BDNF in rats.